Investigating spatial skills and math anxiety as mediators in a sequential mediation model: A pilot study - Lu Wang (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2021)
Prior research showed a gender effect on spatial ability, math anxiety, and math achievement. Lacking, however, is a comprehensive study that testedthe mediation effects of spatial ability and math anxiety between gender and math achievement in a sequential mediation model. To fill this gap, this pilot study tested two mediation relationships, one with spatial ability as a mediator, gender as a predictor, and math anxiety as an outcome variable; the other with math anxiety as a mediator, spatial ability as a predictor, and math achievement as an outcome variable. In addition, the study tested the relative strengths of the relationship between specific spatial skills that included perspective-taking, spatial imagery, and mental rotation and collegiate math achievement that included trigonometry, calculus, and linear algebra) via canonical correlations. Lastly, gender differences in spatial skills, math anxiety, and math achievement were investigated. The results of the independent t-tests showed that none of the well-documented gender differences in spatial ability was found. Canonical correlation analysis showed that a single canonical variable is sufficient in accounting for math-spatial relationship. The sequential mediation model, with spatial ability and math achievement serving as themediators in the model, fitted reasonably well. However, none of the mediation effects was statistically significant. Implications of these findings and future directions of this research are discussed